Targeting Conversational Skills with Digital Storytelling in EFL - Koelzer, Marie-Louise; Christiansen, Sidury (CIEX JOURNAL, 2016)
With the rise of technology, the way we perceive language and literacy has become inherently digital and multimodal. Therefore, it is important for educators to teach language and literacy skills that stretch beyond the use of a paper and pencil. In this article, we will present a digital storytelling (DST) project that EFL educators can implement to help beginning and intermediate learners to improve their conversational skills in formal and informal contexts, but also to provide students with practice of other language and literacy skills through multimodal and digital forms of communication. Finally, we will describe the major implications and drawbacks of DST in the EFL setting.